Non-alcoholic fatty liver disease connections with fat-free tissues: A focus on bone and skeletal muscle - Poggiogalle, Eleonora (World J Gastroenterol, 2017)
The estimates of global incidence and prevalence of non-alcoholic fatty liver disease (NAFLD) are worrisome, due to the parallel burden of obesity and its metabolic complications. Indeed, excess adiposity and insulin resistance represent two of the major risk factors for NAFLD; interestingly, in the last years a growing body of evidence tended to support a novel mechanistic perspective, in which the liver is at the center of a complex interplay involving organs and systems, other than adipose tissue and glucose homeostasis. Bone and the skeletal muscle are fat- free tissues which appeared to be independently associated with NAFLD in several cross-sectional studies. The deterioration of bone mineral density and lean body mass, leading to osteoporosis and sarcopenia, respectively, are age-related processes. The prevalence of NAFLD also increases with age. Beyond physiological aging, the three conditions share some common underlying mechanisms, and their elucidations could be of paramount importance to design more effective treatment strategies for the management of NAFLD. In this review, we provide an overview on epidemiological data as well as on potential contributors to the connections of NAFLD with bone and skeletal muscle.